Ideology, civilian authority and the Zimbabwean military - Tendi, M (Routledge, 2013)
Since 2002, many scholars and Zimbabwean politicians have argued that Zimbabwe's Joint Operations Command (JOC), which comprises the Zimbabwe Defence Forces (ZDF) commander and heads of the army, prisons, police, air force and intelligence, increasingly poses a threat to civilian authority. A notorious statement made by the ZDF commander Vitalis Zvinavashe in 2002 is often cited as evidence of the JOC or military elites' partisan support for President Robert Gabriel Mugabe and his Zimbabwe African National Union Patriotic Front ZANU[PF]) party. This article argues that Zvinavashe's 2002 statement has been interpreted in selective ways, and that external factors that played a crucial part in precipitating his intervention in 2002 have been neglected. This has resulted in an impoverished understanding of the full import of Zvinavashe's 2002 statement. Using Zvinavashe as an example, the article also demonstrates that some military elites' allegiance to Mugabe and ideological commitment to ZANU(PF) rule must be seen as unstable and contradictory. Be that as it may, Mugabe retains effective control of military elites for a variety of reasons, namely power derived from his status as ZDF commander in chief and his high position in ZANU(PF)'s 1970s nationalist hierarchy; his shrewd use of prebends to maintain loyalty; and the staunch ideological commitment of sections of the military elite to ZANU(PF).